1995
DOI: 10.1086/629737
|View full text |Cite
|
Sign up to set email alerts
|

Intracrustal Derivation of Na-Rich Andesitic and Dacitic Magmas: An Example from Volcán Ollagüe, Andean Central Volcanic Zone

Abstract: Andesitic and dacitic lavas erupted from Quaternary stratovolcanoes in the Central Volcanic Zone (CVZ) of the Andes have major and trace element compositions similar to proposed melts of subducted mid-ocean ridge basalt and Na-rich trondjhemites, tonalites, and granodiorites (TTG) in Early Archean high-grade gneiss terrains. Suites of lavas from individual volcanoes have average La/Yb of 25-45, Sr/Y of 30-65, Yb contents of 1.5-1.1 ppm, and Na O contents > 3.8 wt %, with lavas erupted on the volcanic front dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Savo (approximately 14 km; Petterson et al 2003) is much thinner than in those models that involve extensive crustal interaction (Atherton and Petford 1993;Feeley and Hacker 1995). DeLong et al (1975) compiled data for sodic magmas in intra-oceanic arcs and observed that these rock types occur in a number of specific tectonic settings: 1) near lateral edges of subduction zones where hinge faulting is occurring (Bering, Fiji, Grenada) and 2) where fracture zones and ridges are being subducted at a high angle (Kanaga, Aoba and Ambrym, New Georgia, Iwo-jima).…”
Section: Sodic Magmas At Savomentioning
confidence: 94%
See 1 more Smart Citation
“…Savo (approximately 14 km; Petterson et al 2003) is much thinner than in those models that involve extensive crustal interaction (Atherton and Petford 1993;Feeley and Hacker 1995). DeLong et al (1975) compiled data for sodic magmas in intra-oceanic arcs and observed that these rock types occur in a number of specific tectonic settings: 1) near lateral edges of subduction zones where hinge faulting is occurring (Bering, Fiji, Grenada) and 2) where fracture zones and ridges are being subducted at a high angle (Kanaga, Aoba and Ambrym, New Georgia, Iwo-jima).…”
Section: Sodic Magmas At Savomentioning
confidence: 94%
“…Sodic magmas (where Na 2 O−2 > K 2 O) are unusual occurrences in arcs, although they may be generated by a number of mechanisms, including: partial melting of subducted slabs; partial melting of underplated basaltic crust (Atherton and Petford 1993); assimilation of basaltic lower crustal material (Feeley and Hacker 1995); partial melting of mantle metasomatised by aqueous fluids (Kamenov et al 2008;McInnes and Cameron 1994) and/or melts from subducted slabs (Kepezhinskas et al 1995); and small degrees of partial melting of the mantle in truncated melt columns (Hole and Saunders 1996).…”
Section: Sodic Magmas At Savomentioning
confidence: 99%
“…Chondrite and PM values are from Sun and McDonough (1989). Defant and Drummond, 1990) cling lower continental crust in the mantle (e.g., Xu et al, 2002), and/or assimilationfractionation-crystallization (AFC) process (e.g., Feeley and Hacker, 1995). Either partial melting of subducted oceanic slab or AFC of a basaltic magma is unlikely for the Baiqi adakitic rocks based on the following observations.…”
Section: The Case Of Thickened Lower Continental Crust-derived Adakitmentioning
confidence: 97%
“…Three petrogenetic models have been proposed for the generation of adakitic magmas: (1) partial melting of subducting slab (e.g., Defant and Drummond, 1990), (2) partial melting of basaltic lower crust (e.g., Atherton and Petford 1993), and (3) fractionation and contamination of mantle-derived magmas with garnet-bearing lower continental crust (e.g., Feeley and Hacker, 1995).…”
Section: Petrogenetic Model For the Zhantang Adakite-like Andesitic Mmentioning
confidence: 99%
“…Fractionation and contamination of mantlederived magmas with garnet-bearing lower crust was proposed to interpret petrogenesis of the adakite-like rocks in Volcan Ollague, Andean Central Volcanic Zone (Feeley and Hacker, 1995). Garnet as a separated phase rapidly depletes a magma in Y and HREE with little effect on the Sr and LREE contents, and results in high Sr/Y and La/Yb ratios in the residual magma.…”
Section: Petrogenetic Model For the Zhantang Adakite-like Andesitic Mmentioning
confidence: 99%